Perception of patient safety culture among perioperative staff : exploring the roles of individual factors and organizational factors - Yi Lin, Bong; Keng Sheng, Chew; Sze Kiat, Sim; Shalin Wan Fei, Lee; Peter Chee Seong, Tan (BioMed Central Ltd., 2025)
Background Patient safety is a fundamental concern in healthcare, especially in high-risk settings such as operating theaters, where there is an increased likelihood of adverse events. Nonetheless, studies within the operating theater setting remain limited. This study examined the influence of organizational and individual factors, and the moderating effects of job position, gender, and experience toward patient safety culture among perioperative staff at Sarawak General Hospital (SGH) in Malaysia. Methods A cross-sectional study design was employed, involving 137 perioperative staff members, including doctors and nurses, selected through proportionate stratified sampling. The Safety Attitude Questionnaire-Operating Room (SAQ-OR) and Hospital Survey on Patient Safety Culture (HSOPSC) was adapted in this study. The responses were analyzed via descriptive analysis and partial least square-structural equation modeling (PLS-SEM). Results Most respondents (67.2%) were registered nurses. The stress recognition dimension had the highest mean positive response rate at 73.0%, whereas the perceptions of the management dimension had the lowest at 22.6%. The study findings revealed a significant positive relationship between individual factors and the perception of patient safety culture (β=0.389, p=0.008). In contrast, the association between organizational factors and the perception of patient safety culture was positive but not significant (β=0.293, p=0.054). The moderating effects of position (β=0.048, p=0.572), gender (β=0.183, p=0.515), and years of experience in a specialty (β = −0.103, p=0.187) were also nonsignificant. Conclusion Overall, the perception of patient safety culture in the SGH operating theater was perceived as moderate, with substantial room for improvement. The lowest positive response rate in the management dimension implies the need for the organization to address staffing shortage issues and improve workplace support to increase patient safety. Individual factors, such as job satisfaction and stress recognition, were significantly associated with these perceptions. With a coefficient of determination (R²) value of 42.6% in this structural model, additional influencing factors may be relevant. Future studies should explore influences such as government policies, budget allocation, and technological advancements to further enhance patient safety culture in operating theaters.